PEMBELAJARAN ONLINE DI SEKOLAH DASAR: TANTANGAN KESIAPAN GURU DI ERA DIGITAL 4.0 - Ishak Syairozi (Ilma Jurnal Pendidikan Islam, 2022)
The government through the relevant Education Office has instructed to conduct distance learning activities (Online/Online) during the spread of COVID-19. The process is for Jakarta starting March 14, 2020. This incident is not only in Indonesia, in many countries also doing social distancing, limiting social relations. Including school closures and student learning. The learning process in schools was stopped as an effort to prevent the spread of Covid-19, replaced with Home Study (study at home). In this condition, learning to use an online learning system or online between students and teachers. This new learning system raises problems, including; teacher readiness and adaptation, teacher competence, and skills in mastering online learning media (WhatsApp, Classroom, zoom, google meet). To reveal these things, the researchers used the phenomenology research method on the teacher community to answer the existing problems. This study aims to become an awareness of the demands of student learning in the digital 4.0 era, both for students, parents, and teachers in particular, as well as increasing teacher competence as an effort to adapt and exist in the midst of the changing digitalization era.